Methyl jasmonate promotes postharvest ripening and softening of mango and regulates the expression of key genes - ZHANG Shasha; WANG Xin; GUO Pan; ZHANG Jing; MA Dexin; SHAO Yuanzhi; LI Wen (Guoshu xuebao)
[Objective] Mango is renowned as the “King of Tropical Fruits” for its delicious flesh and distinctive flavor. It is a respiratory climacteric fruit that turns yellow and soft after harvest due to a rapid increase in respiratory rate. Ethephon (ETH) induces the generation of endogenous ethylene, thereby achieving the effect of rapidly initiating the ripening process. This process is non-adjustable and irreversible, resulting in excessive over-ripening, softening, and rotting of a large number of fruits. It has become a key factor restricting the development of the mango industry and post-harvest storage and preservation. Therefore, there is an urgent need to study new ripening technologies to address the existing issues and extend the shelf life of mangoes. A significant amount of research have indicated that exogenous methyl jasmonate (MeJA) treatment plays a role in regulating the quality of post-harvest fruits. However, the mechanism of action of the MeJA on mangoes remains unclear. Therefore, this study explored the influence and mechanism of the exogenous MeJA treatment on the quality of post-harvest mango fruits, providing theoretical support for the application of the MeJA in post-harvest storage and preservation of the fruits and offering new ideas to solve the problem of rapid rotting after ethylene treatment. [Methods] The test mango variety was Tainong No. 1 harvested from the mango plantation in Baoping Village, Yazhou District, Sanya City, Hainan Province. Immediately after harvest, they were transported to the laboratory. The diseased and damaged fruits were screened and removed. The fruit stalks were cut off, and they were washed and soaked in 0.1% chlorinated detergent for 20 minutes to remove residual pectin and pathogens. After drying, they were evenly divided into five groups. Different concentrations of the MeJA solutions of 0.5, 1, and 2 mmol·L-1 were used for soaking treatment for 5 minutes, followed by sealing for 20 hours. Ethephon treatment at 0.5 g·L-1 (ETH) and water treatment were used as control groups. The chroma, hardness, ethylene release rate, and TSS physiological indicators of each group of the mangoes during storage were detected. Simultaneously, the effects of 1 mmol·L-1 MeJA on the texture, protopectin content, soluble pectin content of mangoes were determined, and the specific effects on the enzyme activities of key enzymes and the expression levels of key enzyme genes in the cell wall degradation pathway were analyzed in depth. [Results] Compared with the water control group, the 1 and 2 mmol·L-1 MeJA groups both promoted the degradation of chlorophyll, facilitated fruit color transformation, promoted the decrease in hardness, increased the ethylene release rate and soluble solids content, while the effect of the 0.5 mmol·L-1 group was not significant. Both the ETH group and 2 mmol·L-1 MeJA significantly promoted the rapid ripening of the fruits. The 1 mmol·L-1 treatment promoted the color transformation of mango fruits and inhibited the rate of hardness decrease compared with the ETH group. Additionally, compared with the water control group, the 1 mmol·L-1 MeJA could promote changes in the texture of the mangoes, facilitate the decrease in protopectin content and the increase in soluble pectin content, increase the activities of polygalacturonase (PG), pectin methylesterase (PME), pectin lyase (PL), cellulase (CX), and the expression levels of their encoding genes MiPME, MiPL and MiPG. The correlation analysis was conducted on the hardness, texture, enzyme activity, and gene expression levels of the Tainong No. 1 mango fruits after the exogenous MeJA treatment. The PME enzyme activity was significantly and positively correlated with the MiPME2, the correlation between the PL enzyme activity and the MiPL2 gene expression was greater than those of the MiPL1 gene, and MiPG enzyme activity was significantly and positively correlated with the MiPG3 gene expression. [Conclusion] The study showed that after the methyl jasmonate treatment, the differential expression of cell wall degradation enzyme genes would lead to changes in the activities of PME, PL, and PG enzymes, promoting the transformation of protopectin to soluble pectin in the fruit, ultimately resulting in the softening of the mangoes.